RETRACTED: Typology of temperaments "Priority": Sustainable development of the organization due to the increase in the personnel work efficiency - Kosyakov Alexander; Ishkov Alexander (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001